Reliability assessment and sensitivity analysis of concrete gravity dams by considering uncertainty in reservoir water levels and dam body materials - Pouraminian, Majid; Pourbakhshian, Somayyeh; Noroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
An elaborate safety assessment of the Pine Flat (PF) concrete gravity dam (CGD) has been conducted in this paper. Structural analysis was performed by taking into account the uncertainties in the physical and mechanical properties of the dam body materials and the reservoir water level. The coefficient of variation of 5 and 10 percent and the Gaussian distribution (GAUS) are assigned to random variables (RVs).
Keywords: concrete dam; sensitivity analysis; hydrostatic pressure; epistemic uncertainty; failure risk; zapora betonowa; analiza wrażliwości; ciśnienie hydrostatyczne; ryzyko awarii